1995
DOI: 10.1002/j.1537-2197.1995.tb11586.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow hybrid zone between two subspecies of big sagebrush,Artemisia tridentata(Asteraceae). III. Developmental instability

Abstract: Stable hybrid zones are believed to occur because gene dispersal is opposed by selection, but the nature of this selection remains unclear. The dynamic equilibrium model postulates that hybridization disrupts coadapted gene complexes, leading to alterations in development and subsequent hybrid unfitness. Alternatively, the bounded hybrid superiority model assumes that selection is due to exogenous factors. Here, we examine the developmental instability of sagebrush across a narrow hybrid zone. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 58 publications
2
13
0
2
Order By: Relevance
“…Despite significant differences among lines in the level of FA of several traits, no coherent changes in FA with inter-population hybridization were observed across traits, and hybrid progenies were not consistently more, or less, asymmetric than parental lines. These results are consistent with previous studies in which hybrids were either equally or less asymmetric than parental lines (Ferguson et al, 1988;Alibert et al, 1994;Freeman et al, 1995;Gharrett et al, 1999;Debat et al, 2000;Andersen et al, 2002;Rao et al, 2002;see Alibert & Auffray, 2003 for review). However, in several of these studies, signs of heterosis were found in the F1 (e.g.…”
Section: Inter-population Hybrids Fa and Outbreeding Depressionsupporting
confidence: 92%
“…Despite significant differences among lines in the level of FA of several traits, no coherent changes in FA with inter-population hybridization were observed across traits, and hybrid progenies were not consistently more, or less, asymmetric than parental lines. These results are consistent with previous studies in which hybrids were either equally or less asymmetric than parental lines (Ferguson et al, 1988;Alibert et al, 1994;Freeman et al, 1995;Gharrett et al, 1999;Debat et al, 2000;Andersen et al, 2002;Rao et al, 2002;see Alibert & Auffray, 2003 for review). However, in several of these studies, signs of heterosis were found in the F1 (e.g.…”
Section: Inter-population Hybrids Fa and Outbreeding Depressionsupporting
confidence: 92%
“…Manly and Ledig 1979;Graham and Felley 1985;Leary et al 1985). However, other studies have reported no differences between hybrids and parental species (e.g., Felley 1980;Freeman et al 1995). The genotypes of atemoya, the hybrid between A. cherimoya and A. squamosa, did not show an increased level of FA for any of the traits studied in comparison with A. cherimola.…”
Section: Fluctuating Asymmetry In Hybridsmentioning
confidence: 58%
“…For example, most leaves have the same number of leaf‐margin teeth on each side of the blade: 0 or 1 pair in the case of Q. laurina , 2 or 3 pairs in the case of Q. affinis . The presence of asymmetrical leaves with unequal numbers of teeth on each side, particularly in the hybrid zone, could be an indication of developmental instability resulting from the disruption of parental gene complexes (Freeman et al ., 1995).…”
Section: Discussionmentioning
confidence: 99%